From Ritual Practice to Community Resilience: An Ethnographic Study on Local Cultural Strategies in Urban Makassar - Djufri (Indonesian Journal of Social Development, 2026)
The rapid transformation of urban landscapes in Indonesia presents significant challenges to the continuity of local cultural practices, particularly among marginalized urban communities. This study aims to explore how communities in Makassar employ ritual practices as social strategies to build cultural resilience amid spatial, economic, and social pressures. Using a cultural ethnographic approach, fieldwork was conducted across four districts—Tamalate, Tallo, Bontoala, and Barombong—through participant observation, semi-structured interviews with 18 key informants, and spatial documentation of ritual sites. Rituals such as mappacci, makkanre tempo, makkiade, and akkarungeng are examined not merely as traditional expressions, but as adaptive practices that sustain social cohesion and reclaim marginalized urban spaces. The study is grounded in four theoretical frameworks: structuration theory (Giddens), thick description (Geertz), everyday tactics (de Certeau), and third space (Bhabha), to interpret how symbolic actions create spaces for identity negotiation and social resilience. Findings reveal that rituals function as flexible and reflective social systems, enabling communities to foster intergenerational solidarity, preserve collective identity, and creatively respond to urban stressors. These practices are not static; they evolve through digital mediation, spatial innovation, and collective agency. The study concludes that rituals are not merely cultural relics, but dynamic infrastructures of meaning that underpin the resilience of contemporary urban communities. As such, this research bridges the gap between structural approaches to urban resilience and cultural agency in everyday life.